1981
DOI: 10.1051/rnd:19810306
|View full text |Cite
|
Sign up to set email alerts
|

Variations saisonnières de la qualité du sperme chez le bélier Ile-de-France. II. Fécondance : relation avec les critères qualitatifs observés in vitro

Abstract: In the spring, there was a close relationship between the fertility of the ejaculate and its proportion of abnormalities (r = -0.83 ; P < 0.01).Fertility was also related to the percentage of abnormal heads (r = -0.59 ; P < 0.05).In autumn, when the proportion of total abnormalities was much lower and almost exclusi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1
5

Year Published

1983
1983
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 5 publications
(9 reference statements)
1
6
1
5
Order By: Relevance
“…We found in our experiment, above the culling threshold, a permanent and positive relationship between motility and fertility. This small effect contrasts with the absence of effect previously found by Colas (1981) in Ile de France and by Duval et al (1995) in one Lacaune centre even if this centre displayed a lower effect in our study. But this agrees with the important role of this characteristic on the transport and survival of spermatozoa in the female reproductive tract and fertility (Salamon and Maxwell, 2000).…”
Section: Discussioncontrasting
confidence: 56%
“…We found in our experiment, above the culling threshold, a permanent and positive relationship between motility and fertility. This small effect contrasts with the absence of effect previously found by Colas (1981) in Ile de France and by Duval et al (1995) in one Lacaune centre even if this centre displayed a lower effect in our study. But this agrees with the important role of this characteristic on the transport and survival of spermatozoa in the female reproductive tract and fertility (Salamon and Maxwell, 2000).…”
Section: Discussioncontrasting
confidence: 56%
“…In the V breed, no significant variations appeared at any time of the experiment, except in the last month when BW decreased (P < 0.05). However, Thibault, 1956 ;Ortavant, 1958 ;Pelletier, 1971 ;Albério, 1976 ;Colas, 1980Colas, , 1981 (Colyer, 1971 ;Courot, 1971 ;Albério, 1976) En plus du pourcentage total d'anomalies morphologiques, nous avons calculé la proportion de spermatozoïdes porteurs de malformations de la tête (lésions de l'acrosome, micro-ou macro-céphalies, têtes pyriformes ou allongées etc...), connues pour leur effet sur la fécondance (Colas, 19811 et (Ortavant et Thibault, 1956 ;Ortavant, 1958, Pelletier, 1971Albério, 1976 ;Schanbacher, 1979 ;Schanbacher et Ford, 1979 ;Lincoln, 1979 ;Colas et al, 1985) (Fowler, 1965 ;Neves, Günzel et Schmidt, 1980 ;Colas, 1980 ;Mickelsen, Paisley et Dahmen, 1981 ;Amir et al, 1986).…”
unclassified
“…breed or genetic group (Ologun et al, 1981;Chenoweth, 1983). Colas and Guerin (1981) found an association between spermatozoa anomalies with fertility tests in Ile-deFrance rams. However, Galina et al (2007) demonstrated that libido is neither related to semen quality nor to scrotal circumference, so that it is possible to obtain an excellent semen sample in bulls with low libido.…”
Section: Introductionmentioning
confidence: 99%